Fresh food systems in small island economies of the South Pacific - Kulke, Elmar (DIE ERDE – Journal of the Geographical Society of Berlin, 2023)
This study analyzes to what extent small islands in the South Pacific are integrated into global food systems; it shows which different fresh fruits and vegetables are sold, which retail formats are offering which specific assortments, and which supply chains are established. In the small island economies, distance, transport costs, and market volume are much more important than in larger countries of the Global South. Direct marketing for local products is dominating, fresh products which can be transported by using ship-freight-container with lower transport costs are broadly available and the supply with long-distance air-freight imports is very limited due to high transport costs. These products are only sold in areas with high-income households who can afford to buy them. In small and distant economies, the globalization of food systems finds its limits.